New species and reports of dactylogyrids (Monogenoidea) from Salminus franciscanus (Actinopterygii: Bryconidae) from the upper São Francisco River, Brazil - Monteiro, Cassandra Moraes; Cohen, Simone Chinicz; Brasil-Sato, Marilia Carvalho (Zootaxa, 2015)
Six species of dactylogyrid monogenoideans were collected at the upper São Francisco River, State of Minas Gerais, Brazil, from the gills of Salminus franciscanus. Anacanthorus adkruidenieri sp. n. and Anacanthorus paradouradensis sp. n. are described and compared with the other species of Anacanthorus. Anacanthorus adkruidenieri sp. n. is more similar to A. kruidenieri and A. parakruidenieri, but it can be distinguished from both by the rod-shaped accessory piece, which is articulated with the base of the male copulatory organ and is coiled around it, and by the shank of the hook, with expanded proximal bulbous portion bearing a central, elliptical foramen. Anacanthorus paradouradensis sp. n. resembles A. douradensis, but differs in the accessory piece, which is approximately half the length of the copulatory organ. Salminus franciscanus is a new host record and the São Francisco Basin is a new locality record for Anacanthorus daulometrus, Annulotrematoides glossophallus, Jainus iocensis and Tereancistrum arcuatus.